Person-Organization Fit: Sebuah Pendekatan Baru dalam Seleksi Karyawan - Tri Wulida Afrianty (Jurnal Manajemen Maranatha, 2005)
This article describes a new approach to selection in which employees are hired to fit the characteristic of an organization, not just the requirements of a particular job. The hiring practices are changing the traditional selection model. An organizational analysis supplements a job analysis, and personality attributes are screened in addition to skills, knowledge, and abilities. This article also provides the basic steps of the new selection model made by Bowen, Ledford, and Nathan (1991). The new model works to its fullest advantage in organizations that allow employees enough freedom to use their unique attributes to influence job performance.